Smart waste management system for residential area / Nazihah Alway and Asmat Ismail - Alway, Nazihah; Ismail, Asmat (2023)
A growing population, ongoing economic progress, and greater quality of living have resulted in an unavoidable increase in demand and consumption, resulting in a rise in waste generation. Most researchers concentrated primarily on the final treatment, but few paying attentions to the collection and transportation. Besides, people are confronted with the challenges of waste categorisation on Municipal Solid Waste (MSW), in which people must first learn about various forms of waste to properly identify them. Without modern waste detection technologies, effective waste sorting and categorisation takes a longer time. The objectives of this research are to develop smart waste management system design ideas, assemble the proposed smart waste management system, demonstrate the performance of the improved system, and suggest the marketability potential of the proposed system in Malaysia. The research design was qualitative in nature as the data collection method adopted for this study are based on document analysis, literature review, design thinking method, and 3D modelling.